Importance of occupation for SARS-CoV-2 seroprevalence and COVID-19 vaccination among correctional workers in Quebec, Canada: A cross-sectional study - Nadine Kronfli; Nadine Kronfli; Camille Dussault; Mathieu Maheu-Giroux; Alexandros Halavrezos; Sylvie Chalifoux; Hyejin Park; Lina Del Balso; Matthew P. Cheng; Joseph Cox; Joseph Cox; Joseph Cox (Frontiers Media S.A., 2022)
BackgroundCorrectional workers are at increased risk of SARS-CoV-2 infection. We examined the seroprevalence of SARS-CoV-2, determined the effects of carceral and occupational exposures on seropositivity, and explored predictors of COVID-19 vaccine uptake among correctional workers in Quebec, Canada.MethodsWe conducted a cross-sectional seroprevalence study in three provincial prisons. The primary and secondary outcomes were SARS-CoV-2 antibody seropositivity (Roche Elecsys® serology test) and self-reported COVID-19 vaccination status ("fully vaccinated" defined as two doses or prior infection plus one dose), respectively. Poisson regression models with robust standard error were used to examine the effect of occupational variables with SARS-CoV-2 seropositivity and predictors of COVID-19 vaccine uptake. Estimates are presented as crude and adjusted prevalence ratios (aPR) with 95% confidence intervals (95% CI).ResultsFrom 14 July to 15 November 2021, 105/600 (18%) correctional workers tested positive across three prisons (range 11-21%); 76% were fully vaccinated. Seropositivity was affected by prison occupation (aPR 1.59, 95% CI 1.11-2.27 for correctional officers vs. all other occupations) and low perceived concern of SARS-CoV-2 acquisition (aPR 1.62, 95% CI 1.11-2.38 for not/hardly worried vs. somewhat/extremely worried). Predictors of being fully vaccinated included race/ethnicity (aPR 0.86, 95% CI 0.76-0.99 for visible minority vs. White), presence of comorbidities (aPR 1.14, 95% CI 1.02-1.28 for > 2 vs. none), and prison occupation (aPR 0.82, 95% CI 0.73-0.92 for correctional officers vs. all other occupations).ConclusionsCorrectional officers were most likely to have acquired SARS-CoV-2, but least likely to be vaccinated, underscoring the importance of addressing both occupational risks and COVID-19 vaccine hesitancy to mitigate future outbreaks.